Validation of the falls efficacy scale and falls efficacy scale international in geriatric patients with and without cognitive impairment: results of self-report and interview-based questionnaires - Hauer, Klaus; Yardley, L.; Beyer, N.; Kempen, G.; Dias, N.; Campbell, M.; Becker, C.; Todd, C. (Gerontology, 2010)
Background: Frail, old patients with and without cognitive impairment are at high risk of falls and associated medical and psychosocial issues. The lack of adequate, validated instruments has partly hindered research in this field. So far no questionnaire documenting fall-related self-efficacy/fear of falling has been validated for older persons with cognitive impairment or for different administration methods such as self-report or interview. Objective: To validate the self-report and interview version of the Falls Efficacy Scale (FES) and the Falls Efficacy Scale International Version (FES-I) in frail geriatric patients with and without cognitive impairment. Methods: 156 geriatric patients in geriatric rehabilitations wards with (n = 75) and without cognitive impairment (n = 81) were included in this study. Reports of fall-related self-efficacy were based on self-reported and interview-based questionnaires. Descriptive statistics, reliability estimates and validation results were computed for the total group and sub-samples with respect to cognitive status, for the 2 different questionnaires (FES/FES-I) and for the 2 administration methods. Test-retest reliability was tested in a subsample of 62 patients. Results: Internal reliability and test-retest reliability were good to excellent in both the FES and FES-I, with the FES-I showing better internal reliability and the FES better test-retest reliability with respect to cognitively impaired persons. The group of cognitively impaired persons tended to show lower test-retest reliability and mean fall-related self-efficacy and had significantly lower completion rates in self-administered questionnaires. As indicated by significant differences in parameters closely related to falls, such as vertigo, functional performances, fear of falling and history of falls, both the FES and the FES-I showed good construct validity. Effect sizes computed for the above-mentioned groups for fall-related parameters confirmed the results of construct validation. Conclusion: Both the FES as well as the FES-I showed good to excellent measurement properties in persons with and without moderate cognitive impairment. In frail older persons, especially in persons with cognitive impairment, an interview-based administration method is recommended.